2020
DOI: 10.1186/s40478-020-00913-w
|View full text |Cite
|
Sign up to set email alerts
|

The molecular characteristics of spinal cord gliomas with or without H3 K27M mutation

Abstract: Due to the rare incidence of spinal cord astrocytomas, their molecular features remain unclear. Here, we characterized the landscapes of mutations in H3 K27M, isocitrate dehydrogenase 1 (IDH1) R132H, BRAF V600E, and the TERT promoter in 83 diffuse spinal cord astrocytic tumors. Among these samples, thirty-five patients had the H3 K27M mutation; this mutant could be observed in histological grade II (40%), III (40%), and IV (20%) astrocytomas. IDH1 mutations were absent in 58 of 58 cases tested. The BRAF V600E … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
80
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(86 citation statements)
references
References 39 publications
5
80
1
Order By: Relevance
“…In this cohort, nearly all grade IV IMAs were H3K27M mutants (92%), in line with previous reports, which described a range between 38 and 100% of H3K27M-mutant tumors among HG spinal astrocytomas [1,8,17,25,27,32,35,41,42,44,53]. All of the H3F3A mutations identified in our cohort consisted of the recurrent hotspot p.K27M mutation.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this cohort, nearly all grade IV IMAs were H3K27M mutants (92%), in line with previous reports, which described a range between 38 and 100% of H3K27M-mutant tumors among HG spinal astrocytomas [1,8,17,25,27,32,35,41,42,44,53]. All of the H3F3A mutations identified in our cohort consisted of the recurrent hotspot p.K27M mutation.…”
Section: Discussionsupporting
confidence: 91%
“…All of the H3F3A mutations identified in our cohort consisted of the recurrent hotspot p.K27M mutation. We did not find any other mutations in genes encoding histone variants H3.1 or additional H3F3A mutations, in contrast with the recent report by Sloan et al, who reported H3F3A p.G34W in grade II and III spinal cord astrocytomas [43].We did not find TERT promoter mutations among HG IMAs, in contrast with those in the brain, and with two recent studies [1,8]. Alvi et al described distinct prognostic groups of HG IMAs according to the presence of TERT promoter mutations and H3K27M mutations [1].…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…To verify the finding in TCGA dataset, we also enrolled 99 IDH-wild type patients in our CGGA database (Hu et al, 2018;Chai et al, 2019c), including 27 diffuse astrocytic gliomas whose TERT promoter status had been tested by pyrosequencing as previously reported (Chai et al, 2020), and we classified these patients into three groups: Group A, diffuse astrocytic glioma without TERT promoter mutant; Group B, diffuse astrocytic gliomas with TERT promoter mutant; and Group C, glioblastoma.…”
Section: Sample Collectionmentioning
confidence: 92%
“…In addition to histologic features, molecular features, such as IDH and 1p/19q codeletion statues, had also been included in the 2016 WHO classification (Louis et al, 2016). IDH-wild type gliomas, including diffuse astrocytic gliomas (WHO grade II/III) and GBM (WHO grade IV), have a poorer prognosis compared with the same histologic IDH-mutant gliomas (Chai et al, 2020). Recently, growing evidence indicated that some IDH-wild type astrocytic gliomas had similar molecular features and prognosis of IDH-wild type GBM (Yang et al, 2016;Aibaidula et al, 2017;Pekmezci et al, 2017;Wijnenga et al, 2017), suggesting that the specific subgroup of IDH-wild type glioma still needs to be further classified.…”
Section: Introductionmentioning
confidence: 99%